Hybrid 3D structure of poly(d,l-lactic acid) loaded with chitosan/chondroitin sulfate nanoparticles to be used as carriers for biomacromolecules in tissue engineering - Santo, Vitor E. (2010)
In the tissue engineering (TE) field, the concept of producing multifunctional scaffolds, capable not only of acting as templates for cell transplantation but also of delivering bioactive agents in a controlled manner, is an emerging strategy aimed to enhance tissue regeneration. In this work, a complex hybrid release system consisting in a three-dimensional (3D) structure based on poly(d,l-lactic acid) (PDLLA) impregnated with chitosan/chondroitin sulfate nanoparticles (NPs) was developed. The scaffolds were prepared by supercritical fluid foaming at 200 bar and 35 "C, and were then characterized by scanning electron microscopy (SEM) and micro-CT. SEM also allowed to assess the distribution of the NPs within the structure, showing that the particles could be found in different areas of the scaffold, indicating a homogeneous distribution within the 3D structure. Water uptake and weight loss measurements were also carried out and the results obtained demonstrated that weight loss was not significantly enhanced although the entrapment of the NPs in the 3D structure clearly enhances the swelling of the structure. Moreover, the hybrid porous biomaterial displayed adequate mechanical properties for cell adhesion and support. The possibility of using this scaffold as a multifunctional material was further evaluated by the incorporation of a model protein, bovine serum albumin (BSA), either directly into the PDLLA foam or in the NPs that were eventually included in the scaffold. The obtained results show that it is possible to achieve different release kinetics, suggesting that this system is a promising candidate for dual protein delivery system for TE applications.